Measurement and simulation of heat exchange in fractured bedrock using inert and thermally degrading tracers. Issue 2 (3rd February 2017) - Hawkins, Adam J.; Fox, Don B.; Becker, Matthew W.; Tester, Jefferson W.
Abstract: Multicomponent groundwater tracer tests were conducted in a well‐characterized field site in Altona, NY using inert carbon‐cored nanoparticles and a thermally degrading phenolic compound. Experiments were conducted in a mesoscale reservoir consisting of a single subhorizontal bedding plane fracture located 7.6 m below ground surface contained between two wells separated by 14.1 m. The reservoir rock, initially at 11.7°C, was heated using 74°C water. During the heating process, a series of tracer tests using thermally degrading tracers were used to characterize the progressive in situ heating of the fracture. Fiber‐Optic Distributed Temperature Sensing (FODTS) was used to measure temperature rise orthogonal to the fracture surface at 10 locations. Recovery of the thermally degrading tracer's product was increased as the reservoir was progressively heated indicating that the advancement of the thermal front was proportional to the mass fraction of the thermally degrading tracer recovered. Both GPR imaging and FODTS measurements reveal that flow was reduced to a narrow channel which directly connected the two wells and led to rapid thermal breakthrough. Computational modeling of inert tracer and heat transport in a two‐dimensional discrete fracture demonstrate that subsurface characterization using inert tracers alone could not uniquely characterize the Altona field site. However, the inclusion of a thermally degrading tracer may permit accurate subsurface temperature monitoring. At the Altona field site, however, fluid‐rock interactions appear to have increased reaction rates relative to laboratory‐based measurements made in the absence of rock surfaces. Key Points: A narrow channel dominated flow as confirmed via thermal sensors, ground penetrating radar, and numerical models Inert tracers alone produced nonunique estimates of fracture aperture distributions and heat transport Thermally degrading tracer tests indicated the advancement of an induced thermal front